2013
DOI: 10.1007/s10815-013-0128-5
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E (Apo E) gene polymorphisms and recurrent pregnancy loss: a meta-analysis

Abstract: Background Recently, a relationship between recurrent pregnancy loss (RPL) and Apolipoprotein E (Apo E) gene polymorphisms has been proposed. In order to investigate the real association between Apo E polymorphisms and RPL, our meta-analysis was carried out. Methods We estimated the association with RPL risk under dominant and recessive models, in combination with the OR and RR with a 95 % confidence interval (CI), which was used to assess the association between RPL and Apo E polymorphisms. Results According … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…This would be consistent with the observations that APOEε2 and APOEε4 are related to poor repair processes in the brain after insults in adults. 3e7 This interpretation is also supported by a finding in a recent study by Li et al (2014) who found an association between recurrent pregnancy loss and the APOEε2 and APOEε4 alleles in the mother, whereas the APOEε3 polymorphism was interpreted by Li to be a protective factor. 21 Molecular mechanisms explaining a possible increased risk for death after fetal brain injury when APOEε4 is present, may be impaired repair processes following an adverse event in utero, in particular through reduced ability to modulate the inflammatory response.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This would be consistent with the observations that APOEε2 and APOEε4 are related to poor repair processes in the brain after insults in adults. 3e7 This interpretation is also supported by a finding in a recent study by Li et al (2014) who found an association between recurrent pregnancy loss and the APOEε2 and APOEε4 alleles in the mother, whereas the APOEε3 polymorphism was interpreted by Li to be a protective factor. 21 Molecular mechanisms explaining a possible increased risk for death after fetal brain injury when APOEε4 is present, may be impaired repair processes following an adverse event in utero, in particular through reduced ability to modulate the inflammatory response.…”
Section: Discussionmentioning
confidence: 67%
“…3e7 This interpretation is also supported by a finding in a recent study by Li et al (2014) who found an association between recurrent pregnancy loss and the APOEε2 and APOEε4 alleles in the mother, whereas the APOEε3 polymorphism was interpreted by Li to be a protective factor. 21 Molecular mechanisms explaining a possible increased risk for death after fetal brain injury when APOEε4 is present, may be impaired repair processes following an adverse event in utero, in particular through reduced ability to modulate the inflammatory response. Zhang et al, in 2010 pointed to immunoregulatory dysfunction in APOEε4 carriers, and Gale et al (2014) also found that APOEε4 allele carriers differed in their immune responses compared to non-carriers.…”
Section: Discussionmentioning
confidence: 67%
“…However, in our analysis, our results showed that the β-fibrinogen -455G/A polymorphism was not associated with RSA. These results suggested that the β-fibrinogen -455G/A polymorphism was not a risk factor for fetal loss, which was supported by Pihusch et al [32] and Poursadegh Zonouzi et al [33]. With the different outcomes, patient selections have been considered one possible reason.…”
Section: Discussionmentioning
confidence: 68%
“…Although serious damage is presented, the accurate pathogenesis of RSA remains unknown in~50 % of cases [1,33]. There is a strong belief that RSA patients with unknown etiology have a multifactorial condition and that genetic and environmental elements play a key role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation